Women Access and Awareness of Financial Inclusion in Indonesia - Lienggar Rahadiantino; Ariska Nurfajar Rini (Jurnal Ekonomi Pembangunan, 2021)
The financial system plays a role in creating a community economic development, especially overcoming gender disparities. This paper analyzes the effect of mobile phone on the financial inclusion of women's in Indonesia involving data from household surveys provided by the 2014 Family Life Survey. We use the probit model with Ordinary Least Square (OLS) methods and the variable procedure to examine how the role of mobile phone on women's awareness in accessing financial institutions, as well as increasing savings and loan ownership. Our estimation results found that mobile phone penetration significantly increased awareness of women to access formal financial institutions, improve saving behavior, higher credit amount and access mobile banking. Therefore, mobile phone brings great benefits in increasing financial inclusion, especially women in Indonesia.